Gender and leisure : social and cultural perspectives - Aitchison, Cara (Routledge, 2003)
"The highly contested nature of both 'gender' and leisure' encapsulates many of the most critical social and cultural debates of the early twenty-first century. Drawing on a wide range of theoretical perspectives, as well as extensive original empirical research, Gender and Leisure offers new insights into social and cultural explanations of the theories, policies and practices that serve to produce, legitimise, reproduce and rework gender and leisure in everyday life."--Jacket